The Efficacy of Podcast in EFL Learning: A Systematic Literature Review - Khoiriyah, Nisa; Ummah, Nasihatul; Hidayani, Selnistia (Universitas Tanjungpura, 2024)
This study explores the effectiveness of podcasts in enhancing English language skills for EFL learners. A systematic literature review was employed to analyze research published between 2019 and 2024. The findings reveal podcasts as a versatile tool, potentially improving various language skills. Listening comprehension emerged as a particular strength, with studies showing increased student engagement and understanding. Exposure to native speakers through podcasts can also benefit speaking fluency, accuracy, vocabulary, and pronunciation. Combining podcasts with activities like podcast creation or self-awareness training can further refine speaking and pronunciation skills. Overall, podcasts offer a promising and engaging approach for EFL instruction. However, their effectiveness depends on targeted skills, learning context, and curriculum integration. While limitations exist, the potential benefits of podcasts for motivation, engagement, and language development make them a valuable asset in the modern EFL classroom.